FUZZY LOGIC TOOLS Reference Manual v1.0 - Barragán Piña, Antonio Javier (Alonso Barba, 2012)
FLT is a C framework for storage, analysis and design of fully general Takagi-Sugeno fuzzy control systems. FLT is designed to store general TS fuzzy systems, without restriction on size of input and output vectors. FLT nor limit the type or distribution of the membership functions used, even it allows mixing of different membership functions in the same antecedent. The biggest advantage of FLT are the implemented functions for the analysis and design of TS fuzzy system.